Overmodulation Control in the Optimization of a H-PDLC Device with Ethyl Eosin as Dye - Manuel Ortuño; Marina Riquelme; Sergi Gallego; Andrés Márquez; Inmaculada Pascual; Augusto Beléndez (International Journal of Polymer Science)
The response of a H-PDLC device is improved by means of a two-step method. First, component optimization—initiator system, crosslinker, and cosolvent—enables the diffraction efficiency of the hologram to be maximized. Second, the use of N-methyl-2-pyrrolidone in combination with N-vinyl-2-pyrrolidone prevents the overmodulation in photopolymers containing ethyl eosin.